Legal Implications in Human Resource Management: A Study of Employment Policy - ita, april; Kurniasi, Ririn (IAHN Tampung Penyang Palangka Raya, 2024)
Human Resources (HR) management in an organization does not only focus on developing employee competence and performance, but also must comply with various applicable labor regulations. This research aims to analyze legal implications in human resource (HR) management with a focus on employment policy in Indonesia. In the era of globalization, HR management is one of the key factors in maintaining a company's competitiveness. Through literature review and data analysis, this research identifies the challenges and opportunities faced by companies in implementing employment policies that comply with applicable legal regulations. The purpose of this research is to provide insight into legal compliance and risk management in the HR context. The research results show that compliance with labor regulations not only improves employee welfare but also strengthens the company's reputation.